2010
DOI: 10.1590/s1516-89132010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Reserve carbohydrates and lipids from the seeds of four tropical tree species with different sensitivity to desiccation

Abstract: Considering the importance of water content for the conservation and storage of seeds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
1
26
0
3
Order By: Relevance
“…As shown by Mello et al (2010), lipids in cotyledons of C. echinata represent more than 17 percent of DM, whereas linoleic acid represents nearly half of them (more than 45 percent). Respiration using carbohydrates produces respiratory quotient (RQ) close to 1.0 since carbohydrate oxidation (highly oxygenated substrates) involves equal amounts of carbon dioxide and oxygen.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown by Mello et al (2010), lipids in cotyledons of C. echinata represent more than 17 percent of DM, whereas linoleic acid represents nearly half of them (more than 45 percent). Respiration using carbohydrates produces respiratory quotient (RQ) close to 1.0 since carbohydrate oxidation (highly oxygenated substrates) involves equal amounts of carbon dioxide and oxygen.…”
Section: Discussionmentioning
confidence: 97%
“…These oxidative reactions could explain the low viability of C. echinata seeds while stored at temperatures higher than the freezing ones, even when they have low water content, as described by Barbedo et al (2002) and Hellmann et al (2006). Moreover, great amounts of linoleic acid were found in C. echinata cotyledons, (Mello et al 2010), which is a polyunsaturated fatty acid (PUFA) and is particularly susceptible to oxidation by singlet oxygen ( Our results provide evidence on the damage caused by oxidative reactions as revealed by tetrazolium tests performed on seeds based upon different hydration treatments as well as different temperatures. In this work, the target levels of controlled seed hydration covered two energetic states of water (Vertucci & Farrant 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acids composition may vary among species due to the genetic load and climate conditions, and it may also vary among storage tissues. However, in oily seeds palmitic, oleic, and linoleic acids can reach higher amounts of up to 60% of the seeds mass (MELLO et al, 2010). According to Graham (2008), linoleic acid (linoleate) is an important precursor of other polyunsaturated fatty acids and is essential in mammal diets.…”
Section: Resultsmentioning
confidence: 99%
“…Among the soluble sugars, the sucrose is one of the most accumulated in seeds and plays important role in the tolerance to cellular desiccation (Hincha et al, 2006 In studies of carbohydrates reserve composition, Mello et al (2010) have found that in seeds of Erythrina speciosa Andr., sucrose was not the main accumulated sugar. However, the same authors have observed high quantities of oligosaccharides of the raffinose (C 18 H 32 O 16 ) family, associated to tolerance to desiccation.…”
Section: Revista Brasileira De Sementes Vol 34 Nº 4 P 580 -588 2012mentioning
confidence: 99%